Perinatal Asphyxia and Associated Factors among Neonates Admitted to a Tertiary Hospital in Chattogram, Bangladesh (Journal of Chittagong Medical College Teachers' Association, 2023)
Background: Perinatal Asphyxia (PNA) continues to be a significant clinical concern around the world as the consequences can be devastating. While the incidence, risk factors and outcomes of PNA have been characterized in developed countries, less is known in low resource settings. This study aimed to evaluate the risk factors of PNA and outcomes of this condition among neonates admitted in a tertiary hospital in the southeastern part of Bangladesh.Materials and methods: The observational study included 500 consecutively admitted neonates (With PNA, n=188 and without PNA=312) in the neonatal unit of ChattogramMaa-O-Shishu Hospital, Bangladesh from March 2020 to April 2021. Information regarding sociodemography, peri-natal history (Including antepartum, intrapartum and fetal risk factors) were collected by face to face interview and reviewing the medical records on a case record form. In-hospital outcome data were recorded and compared between two groups.Results: Significant risk factorsfor PNA were maternal medical disorders during pregnancy (aOR:2.58, 95% CI, 1.45-4.61) preterm labour (aOR:2.83, 95% CI, 1.21-6.60) home vagianl delivery (aOR:2.78, 95% CI, 1.76-4.40), meconium stained liquor (aOR:3.08, 95% CI, 1.80-5.26), and birth weight less than 2500 g. The predischarge mortality rate was 7.4% in the PNA group and risk of mortality was 2.87 times higher in babies with PNA (OR: 2.87, 95% CI, 1.27-6.49) compared to the baby without PNA.Conclusion: Identified obstetric and neonatal risk factors for PNAcould have been prevented or managed even with our limited resources. Focus on early identification and timely treatment of PNA could reduce related mortality.JCMCTA 2023 ; 34 (1) : 36-40